2000
DOI: 10.1191/026921600667691270
|View full text |Cite
|
Sign up to set email alerts
|

Palliative day care: what do services do?

Abstract: Palliative day care has expanded rapidly in the recent years, but the types of care available vary. To understand more about the different models of day care we conducted a questionnaire survey of the 43-day care centres in North and South Thames Regions in England (total population 13.75 million). The questionnaire covered: management, staffing and organizational policies; the numbers, types and reasons for referral; and the services and care provided. Forty (93%) centres responded. Centres had operated for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 11 publications
(16 reference statements)
1
79
0
5
Order By: Relevance
“…There were eight studies from the UK [9,10,11,12,13,14,15,16,17] and four studies describing palliative day care services in the US [2,4,5,7]. The published literature highlights the differences in services provided at individual day centres.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There were eight studies from the UK [9,10,11,12,13,14,15,16,17] and four studies describing palliative day care services in the US [2,4,5,7]. The published literature highlights the differences in services provided at individual day centres.…”
Section: Introductionmentioning
confidence: 96%
“…The activities provided are similar at each centre: arts and crafts, personal care, baths, cooked meals, massage and relaxation [9,11]. Researchers have highlighted the variability in the aims and organisation of the different services [16,17] and suggested that variations in services depend upon the interests and motivations of those who run the centres rather than local need [13].…”
Section: Introductionmentioning
confidence: 99%
“…SPDC units provide support to patients and their carers and aim to increase continuity of care between inpatient and homecare settings [2], and help patients remain at home for as long as they wish [3]. In recent years there has been a notable increase in the number of units providing this service [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the multidisciplinary teamwork (MDT) approach is emphasised in all SPDC units, observational studies have found that different models of day care exists. [4,11] Traditionally, day care has been based on a social model, where the primary emphasis is on social interaction and carer respite rather than specific goal-orientated therapies. The aim is to provide an environment where patients have the opportunity to socialise with peers while participating in a range of recreational activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation